Cost-benefit analysis of a trans-Arctic alternative route to the Suez Canal: a method based on high-fidelity ship performance, weather, and ice forecast models - Li, Zhiyuan; Ding, Li; Huang, Luofeng; Ringsberg, Jonas W.; Gong, Hui; Fournier, Nicolas; Chuang, Zhenju (MDPI, 2023)
Climate change in recent years has produced viable shipping routes in the Arctic. However, critical uncertainties related to maritime operations in the Arctic make it difficult to predict ship speeds in ice and, thus, the voyage time and fuel costs. Cost–benefit analysis of alternative Arctic routes based on accurate environmental condition modeling is required. In this context, this paper presents a holistic approach that considers the major voyage-related costs of a trans-Arctic route as an alternative to the conventional routes via the Suez Canal Route (SCR) for existing merchant ships. This tool is based on high-fidelity models of ship performance, metocean forecasting, and a voyage optimization algorithm. Case studies are performed based on a general cargo vessel in operation to quantify realistic expenses inclusive of all the major operational, fuel, and voyage costs of the specific voyages. A comparison is made between the total costs of the trans-Arctic route and SCR for different seasons, which proves the economic feasibility of the trans-Arctic route. Overall, this work can provide valuable insights to help policymakers as well as shipbuilders, owners, and operators to assess the potential cost-effectiveness and sustainability of future Arctic shipping, thereby better developing future strategies.
Keywords: arctic shipping; Northern Sea Route; cost–benefit analysis; Weather and Ice Forecast Models; ice resistance; simulation; icebreaker tariff